Characterization of the somatostatin system in tilapia: implications for growth and reproduction - Mizrahi, Naama; Hollander-Cohen, Lian; Atre, Ishwar; Shulman, Miriam; Campo, Aurora; Levavi-Sivan, Berta (Frontiers in Endocrinology, 2024)
Somatostatin (SST) plays diverse physiological roles in vertebrates, particularly in regulating growth hormone secretion from the pituitary. While the function of SST as a neuromodulator has been studied extensively, its role in fish and mammalian reproduction remains poorly understood. To address this gap, we investigated the involvement of the somatostatin system in the regulation of growth and reproductive hormones in tilapia. RNA sequencing of mature tilapia brain tissue revealed the presence of three SST peptides: SST6, SST3, and low levels of SST1. Four different isoforms of the somatostatin receptor (SSTR) subfamily were also identified in the tilapia genome. Phylogenetic and synteny analysis identified tiSSTR2-like as the root of the tree, forming two mega clades, with SSTR1 and SSTR4 in one and SSTR2a, SSTR3a, and SSTR5b in the other. Interestingly, the tiSSTR-5 isoforms 5x1, 5x2, and 5x3 were encoded in the sstr3b gene and were an artifact of misperception in the nomenclature in the database. RNA-seq of separated pituitary cell populations showed that SSTRs were expressed in gonadotrophs, with sstr3a enriched in luteinizing hormone (LH) cells and sstr3b significantly enriched in follicle-stimulating hormone (FSH) cells. Notably, cyclosomatostatin, an SSTR antagonist, induced cAMP activity in all SSTRs, with SSTR3a displaying the highest response, whereas octreotide, an SSTR agonist, showed a binding profile like that observed in human receptors. Binding site analysis of tiSSTRs from tilapia pituitary cells revealed the presence of canonical binding sites characteristic of peptide-binding class A Gprotein-coupled receptors. Based on these findings, we explored the effect of somatostatin on gonadotropin release from the pituitary in vivo. Whereas cyclosomatostatin increased LH and FSH plasma levels at 2 h post-injection, octreotide decreased FSH levels after 2 h, but the LH levels remained unaffected.Overall, our findings provide important insights into the somatostatin system and its mechanisms of action, indicating a potential role in regulating growth and reproductive hormones. Further studies of the complex interplay between SST, its receptors, and reproductive hormones may advance reproductive control and management in cultured populations.